Family Needs Fulfillment Among Poor Single Mothers as Family Hope Program Beneficiaries: A Case Study in Sukajaya, Tarogong Kidul, Garut Regency - Suharma Suharma; Bambang Rustanto; Tuti Kartika; Susilawati Susilawati; Dwi Yuliani; Aryohaji Istyawan (Institute of Multidisciplinary Research and Community Service, 2026)
The substantial number of single mothers in Indonesia reflects a significant dual-role burden, as they must simultaneously serve as economic providers and primary caregivers for their families. While prior studies have examined the economic impact of the Family Hope Program (PKH) or the psychological resilience of single mothers separately, few have integrated both dimensions within a single analytical framework. This study addresses that gap by asking: How do poor single-mother PKH beneficiaries fulfill the five pillars of family needs (physical, economic, educational, social, and emotional) in Sukajaya, Tarogong Kidul, Garut Regency? Using a qualitative case study approach, data were collected through in-depth interviews, passive participant observation, and documentation from six core and two supporting informants, and analyzed using the Miles and Huberman model. Findings reveal that PKH cash assistance substantially strengthens physical food security and children's access to education, effectively preventing school dropout. However, single mothers remain highly vulnerable in the emotional and social domains, experiencing chronic burnout, persistent social stigma, and time poverty that constrains parenting quality. The study concludes that cash transfers alone are insufficient; holistic policy synergy, combining clinical social work interventions, independent economic empowerment, and community-based peer-support groups, is essential to sustainably strengthen single-mother family resilience. Keywords: Poor single mothers, Family hope program, Family needs fulfillment, Dual role, Garut.